VISUAL CULTURE AS A MEANS OF FORMING A COMMON AND PROFESSIONAL CULTURE OF A PERSON - N. V. Syrova; V. N. Chikishev (Вестник Мининского университета, 2018)
Introduction. The article is devoted to the analysis of the visual culture, which forms the general and professional culture of a person in many ways. Attention is paid to the culture of perception of visual images, the ability to analyze them, evaluate, compare, also the features of visual thinking and creative activity, directly relating to it, are considered. The mastering of visual culture is grounded by the specificity of various creative specialties and is a component of the educational process.Materials and Methods. The theory of personality formation and development is the methodological basis of the article. During the research, the analysis of the scientific and theoretical concept of "visual culture" in the system of general and professional human culture was used.Results. The article illustrates that the artistic vision, developed in the process of visual culture formation, starting from childhood, actively participates in the preparation of the ground for the origin of an artistic image, which is realized in the material later. With the development of the creative imagination of the learner, also the development of thinking and memory takes place inevitably, that is harmonization of all parts of the brain is carried out, and this process must be taken into account in the upbringing and education, the formation of the personality, and the formed visual culture is the basis for the improvement of all verges of the student's creative abilities.Discussion and Conclusions. The conclusion is made that visual culture being an integral part of the educational process is the necessary condition for entering the sociocultural space. The education of a high level of visual culture in a modern information and technically replete society is one of the necessary components of the formation of a general and professional culture of a person and it is desirable to begin this process with a student, and even better, from school-days.